The effect of body massage lying face down on intraocular pressure in normal eyes - Jose E.E. League, MD; Jonathan A. Rivera, MD; Edgar U. Leuenberger,MD (Philippine Journal of Ophthalmology)
Objective: This study determined changes in intraocular pressure (IOP) of normal eyes during face-down body massage.